Complete Repair of Massive, Retracted, and “Non-Repairable” Tears of the Rotator Cuff: The Anatomic Vector Repair - Whyte, Graeme P. (Arthrosc Tech, 2020)
Massive and retracted tears of the supraspinatus and infraspinatus tendons of the rotator cuff are associated with great pain and disability and may be considered “non-repairable,” depending on the extent of injury and the experience of the treating clinician. The technique of anatomic vector repair of the rotator cuff is a surgical treatment method that enables the surgeon to accurately characterize the injury pattern and successfully repair many of these debilitating injuries anatomically in a stepwise manner, often in cases that would have otherwise been treated with a less preferable surgical procedure that does not restore native anatomy.